2021
DOI: 10.1039/d1sc00105a
|View full text |Cite
|
Sign up to set email alerts
|

Towards the rational design of ylide-substituted phosphines for gold(i)-catalysis: from inactive to ppm-level catalysis

Abstract: The implementation of gold catalysis into large-scale processes suffers from the fact that most reactions still require high catalyst loadings to achieve efficient catalysis thus making upscaling impractial. Here, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 61 publications
2
31
0
6
Order By: Relevance
“…Recently, we reported on transition metal catalysts based on ylide‐functionalized phosphines (YPhos) [8] . In gold(I)‐catalyzed transformations with moderately ( A ) [8a] as well as highly electron‐rich ( B and C ) [9] YPhos systems exceptionally high turnover numbers were observed. All of these YPhos catalysts so far have relied on triphenyl phosphonium groups which likewise foster arene–gold interactions, thus contributing to the stability and high catalytic performance of the corresponding LAu(I) + species.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported on transition metal catalysts based on ylide‐functionalized phosphines (YPhos) [8] . In gold(I)‐catalyzed transformations with moderately ( A ) [8a] as well as highly electron‐rich ( B and C ) [9] YPhos systems exceptionally high turnover numbers were observed. All of these YPhos catalysts so far have relied on triphenyl phosphonium groups which likewise foster arene–gold interactions, thus contributing to the stability and high catalytic performance of the corresponding LAu(I) + species.…”
Section: Introductionmentioning
confidence: 99%
“…From this structure, the buried volume was calculated using SambVca . The obtained buried volume of 42.5% is lower than that of other acyclic YPhos ligands with PCy 3 or PPh 3 moieties, which usually showed volumes of approximately 50%. Furthermore, the steric map of L1 shows areas of steric bulk only on one side of the of the ligand, namely, the phosphonium moiety. The cyclohexyl groups are unable to reach toward the metal center.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this ylide group and its strong electron-donating abilities, these phosphines exhibited strong electron-donating capabilities, with donor capacities surpassing those of simple phosphines and NHCs. These ligands were shown to be ideal scaffolds for catalytic applications, ranging from gold-catalyzed hydroamination and cyclization reactions to palladium catalysis, such as Buchwald–Hartwig aminations as well as Negishi couplings and α-arylation reactions under mild conditions . Recently, it has been shown that YPhos palladium catalysts are even capable of directly coupling aryl chlorides and alkyl lithium reagents, giving very high selectivities while supplementing the need for any additional transmetalation reagents …”
Section: Introductionmentioning
confidence: 99%
“…[b] Values taken from reference [8a]. [c] Values taken from reference [9a]. [d] Values taken form reference [10].…”
Section: Resultsmentioning
confidence: 99%
“…[7] Recently,wereported on transition metal catalysts based on ylide-functionalized phosphines (YPhos). [8] In gold(I)catalyzed transformations with moderately (A) [8a] as well as highly electron-rich (B and C) [9] YPhos systems exceptionally high turnover numbers were observed. All of these YPhos catalysts so far have relied on triphenyl phosphonium groups which likewise foster arene-gold interactions,t hus contributing to the stability and high catalytic performance of the corresponding LAu(I) + species.…”
Section: Introductionmentioning
confidence: 99%